Synthesis of bioactive Mercury-Picrate Analogue: Synthesis, Characterization, and Biomedical Applications (Journal of Medical & Health Sciences Review, 2025)
Synthesis, characterization, and biomedical applications of mercury complexes stabilized by multinuclear aromatic compounds are investigated in this study. Through use of sulfur rich and aromatic ligand frameworks mercury complexes with increased stability, bioactivity and imaging capabilities were developed. Successful complexation was confirmed via comprehensive analyses including spectroscopic and structural characterization, and because these complexes are robust physicochemical properties, we successfully formed complexes. In biological evaluations, we discovered high antibacterial activity against multidrug resistance strains and potent anticancer effects for the Hg analogs, with Hg-An-3 being the most selective and efficacious. Finally, the complexes proved to be promising as agents for MRI contrast, characterized by high relativity and specificity for subsequent diagnostic imaging. Nevertheless, toxicity evaluations suggested difficulties associated with systemic toxicity and hemolytic effects that require future optimization of ligand design and biocompatibility. The dual therapeutic and diagnostic potential of mercury complexes highlighted by this research should be followed by addressing toxicity if the mercury complexes are to be clinically translated. These findings will help in the development of other interdisciplinary efforts to design efficient mercury based theranostic agents.